2019
DOI: 10.1111/ijlh.13140
|View full text |Cite
|
Sign up to set email alerts
|

Does body position before and during blood sampling influence the Athlete Biological Passport variables?

Abstract: The Athlete's Biological Passport (ABP) is a tool for the indirect detection of blood doping. Current guidelines from the World Anti-Doping Agency (WADA) require a delay of 2 hours after any physical exercise and to be seated for 10 minutes prior to any blood sampling to obtain a valid measurement.Since body position prior to and during phlebotomy may influence the outcome, this study compared blood biomarker variations with changes in body position during blood sample collection. Ten successive venous blood s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…The period of influence these factors had ranged from a few minutes (e.g. body position during sampling [13]) to a few hours (e.g. intense exercise [14]), and can, therefore, alter blood variables.…”
Section: Methodological Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The period of influence these factors had ranged from a few minutes (e.g. body position during sampling [13]) to a few hours (e.g. intense exercise [14]), and can, therefore, alter blood variables.…”
Section: Methodological Approachmentioning
confidence: 99%
“…One group of swimmers lived high and trained high (LHTH, n = 10) for three to four weeks at 2130 m or higher, while a control group (n = 10) completed a three-week training camp at sea level. Haematological parameters were determined weekly three times before and four times after the training camps (+7, +14, +21 and +28 d)measured in13 elite cyclists during and 10 d after 3 weeks of sea level or altitude training (2760 m). The altitude group participated in a 3-week natural altitude training camp at Passo dello Stelvio, Italy, living at 2760 m and training during the majority of ride time > 1800 m for 2-6 h d −1 .…”
mentioning
confidence: 99%
“…For instance, the influence of the tested athlete's body position before and during the blood sampling procedure was assessed, indicating that %RET was unaffected while values measured for the hemoglobin concentration [Hb] and the hematocrit (Hct) differed slightly yet significantly, depending on the tested person's prior activity and body position. Consequently, a seated position for 5–10 min is recommended to obtain ABP data exempt from activity‐ or supine‐induced plasma volume (PV) shifts 181 . Studies on the potential influence of the menstrual cycle on ABP parameters indicated merely negligible effects 182 ; hyperhydration was shown to have no impact on ABP readings 183 ; and likewise, exercise‐induced sweating dehydration with an average loss of up to 3.1% of body mass was reported to have no effect on [Hb] during ABP testing, 184 demonstrating the robustness of the hematological module.…”
Section: Manipulation Of Blood and Blood Componentsmentioning
confidence: 99%
“…Consequently, a seated position for 5-10 min is recommended to obtain ABP data exempt from activity-or supine-induced plasma volume (PV) shifts. 181 Studies on the potential influence of the menstrual cycle on ABP parameters indicated merely negligible effects 182 ;…”
Section: Manipulation Of Blood and Blood Componentsmentioning
confidence: 99%
“…First, blood sample quality is paramount as there is a potential influence of pre-analytical procedures (e.g. position during sampling, sample transport) on the analytical results (Ahlgrim et al, 2010;Robinson et al, 2011;Ashenden et al, 2014;Astolfi et al, 2020). There are strict WADA guidelines for blood collection, transportation and storage to prevent variations due to such confounders (WADA, 2019b;a;c).…”
Section: Introductionmentioning
confidence: 99%